Association between DRD2/ANKK1 rs1800497 C > T polymorphism and post-traumatic stress disorder susceptibility: a multivariate meta-analysis - Niu, Yu-Ming; Zhang, Jie; Tang, Hong; Cao, Lu-Hua; Jiang, Ting-Yun; Hu, Yuan-Yuan (Frontiers in Neuroscience, 2023)
Background: Previous studies have suggested that the DRD2/ANKK1 rs1800497 C>T polymorphism plays a critical role in the risk of post-traumatic stress disorder (PTSD). However, published data are inconsistent or even contradictory. Therefore, we conducted a meta-analysis to explore the underlying correlation between the rs1800497 C>T polymorphism and PTSD risk. Materials and Methods: Five online databases were searched, and all related studies were reviewed up to October 1, 2022. Critical information was extracted, and quality assessment was conducted for all included studies. Multivariate meta-analyses were performed for the genetic model choice, and the odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated to examine the statistical power of the genetic models. In addition, heterogeneity, sensitivity, cumulative analysis, and publication bias were analyzed to guarantee statistical power. Result: Overall, 12 observational studies involving 5,515 subjects were included and analyzed in this meta-analysis. Multivariate analysis indicated that a co-dominant genetic model was most likely choice. Pooled results revealed an elevated PTSD risk in mutated homozygote TT carriers in the general population (TT vs. CC: OR=1.73, 95% CI=1.14-2.62, P=0.01, I2=58.9%) and other specific subgroups. Moreover, similar results were observed in other genetic models using univariate analysis. Conclusion: Current evidence suggests that the DRD2/ANKK1 rs1800497 C>T polymorphism may contribute to PTSD susceptibility.